Pengaruh Kepemimpinan Demokratis Kepala Sekolah, Motivasi Berprestasi Guru terhadap Profesional Kerja Guru di Sekolah Dasar Negeri - Rusmeni Rusmeni (CV. Syntax Corporation Indonesia, 2023)
This study generally aims to examine the influence of democratic leadership and achievement motivation on the professional work of elementary school teachers in Ciledug District, Tangerang City. This study used qualitative methods using causal surveys with a path analysis approach. Dissemination of instruments in the form of questionnaires to collect data on the professional influence of teacher work and coordination of school principals on the quality of education services in SDN in Cipondoh District, Tangerang City. The results of this initial observation are in line with what was stated by Masanah that there is a positive and significant influence of achievement motivation on the professional competence of teachers in SD Negeri in Bonang District, Demak Regency by 86.20%. This positive influence means that if teachers have high achievement motivation in carrying out their duties, the teacher's professional competence will increase.